AN ANALYSIS OF CODE MIXING AND CODE SWITCHING USED ON BOY WILLIAM TALK SHOW IN HIS YOUTUBE CHANNEL - Sudianthi, Ni Komang Ayu; Putri, K. I. M.; Santi, N. P. (Universitas Pendidikan Ganesha, 2020)
AbstractÂ This study discussed about code switching and code mixing used on Boy William YouTube Channel. The purpose of the study is to analyze the type of code-switching and code mixing in two videos in Boy William YouTube channel and to find out the reasons to do code-switching and code mixing on his talk show program. The type of this study is descriptive qualitative research. The subject of the study is 2 videos, video 1 is the talk show with Chelsea Islan in #nebengboy# program and video 2 is the talk show with Nikita Mirzani in #drinkwithboy# program. The data was taken from the transcript of the conversation in the talk show. The most dominant type of code switching in video 1 is inter-sentential type, the second type was intra- sentential type and the third type was emblematic switching. In video 2, the most dominant type is intra-sentential type, the second type was inter-sentential type and the third type was emblematic switching. In code mixing analysis found that in video 1, the most dominant type is alternation, the second type is insertion, the third type is congruent lexicalization. Meanwhile, in video 2, the most dominant type is insertion, the second type is alternation, the third type is congruent lexicalization. In this study, the most dominant reason was talking about particular topic.Keywords: code switching, code mixing, reasons, code, lexicalization